Building up uniqueness within institutional, tourism-related home pages - Bugnot-Tripoz, Miren Aingeru (My University, 2016)
Institutional web sites put together and display a country image which represents a “decisive business card” as stated by Bonhomme & Stalder (2006, 1). Beerli & Martin (2004, 3) detail the dimensions and attributes of the perceived destination image by including a number of tangible items. However, there are a number of intangible factors that cluster mere facts together through symbols, stereotypes and affects and lead to the creation of impressions. European institutional home pages promoting their country look very much alike but still, the destination is generally perceived as unique. To study how this perception has been brought about, our descriptive method will result in a qualitative research concerning discourse and how it has been put into action in institutional web pages for that purpose. By studying the websites of three different European countries - and their addressees - belonging each to a specific language and cultural community, we aim to demonstrate how the claim to uniqueness is introduced by means of a complex semiology, meaningful argumentative strategies and subjective markers.
Keywords: Páginas Web; Análisis del discurso